2013
DOI: 10.5897/ajpp2013.3584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forsythoside on lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages

Abstract: Forsythoside (FS) is an active component of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…FTA significantly downregulated the expression of TRPV1 in hypothalamus and DRG of the yeast-induced fever mice, inhibited MAPKs activation of the hypothalamus and DRG, and then decreased secretion ofPGE2 ( Liu et al, 2017a ). Recent studies have shown that forsythoside can significantly reduce TNF-α secretion in LPS-stimulated RAW 264.7 cells, suggesting that it can reduce TNF-α secretion to relieve fever ( Guan et al, 2013 ). FTA can also suppress LPS-mediated induction of the TLR4 pathway.…”
Section: Single Chinese Herbal Medicines In the Treatment Of Fevermentioning
confidence: 99%
“…FTA significantly downregulated the expression of TRPV1 in hypothalamus and DRG of the yeast-induced fever mice, inhibited MAPKs activation of the hypothalamus and DRG, and then decreased secretion ofPGE2 ( Liu et al, 2017a ). Recent studies have shown that forsythoside can significantly reduce TNF-α secretion in LPS-stimulated RAW 264.7 cells, suggesting that it can reduce TNF-α secretion to relieve fever ( Guan et al, 2013 ). FTA can also suppress LPS-mediated induction of the TLR4 pathway.…”
Section: Single Chinese Herbal Medicines In the Treatment Of Fevermentioning
confidence: 99%
“…TRPV1 is a non-selective cation channel gated by noxious heat, playing major roles in thermoregulation. FT-A alleviated fever of yeast-induced pyrexia mice via suppression of TRPV1 expression and activation, inhibition of MAPKs, activation of the hypothalamus and DRG, and subsequently decreased secretion of pyretic cytokine as PGE2 and IL-8 ( Liu et al., 2017 ).In addition, FT-A can significantly enhance the phagocytic function of macrophages in LPS-stimulated ra-w264.7 cells and reduce the secretion of TNF-α ( Guan et al., 2013 ). FT-A can also inhibit TNF-α and NF-κB by blocking the LPS/TLR4 signaling pathway ( Zeng et al., 2017 ).…”
Section: Fevermentioning
confidence: 99%